Agency and social capital in Chinese international doctoral students' conversion to Christianity. Issue 12 (15th October 2017) - Ding, Qun; Devine, Nesta
Abstract: Chinese international students constitute the largest proportion of overseas students in several English-speaking countries such as the UK and New Zealand. Little research has been done concerning those undertaking doctoral study. This qualitative study explores how Chinese overseas doctoral students become involved in church communities and how some of them convert to Christianity in New Zealand. In-depth interviews were conducted with nine Chinese doctoral students from different social backgrounds. Five of these reported varying degrees of interest in and commitment to Christianity. Their narratives revealed that their conversion was a gradual and complex process as a result of the interplay between habitus, agency and contextual factors. These findings from a New Zealand context provide insights into non-academic experience of Chinese international students, particularly their religious experience.